2013
DOI: 10.1007/s13238-013-3084-z
|View full text |Cite
|
Sign up to set email alerts
|

Mutual regulation between Hippo signaling and actin cytoskeleton

Abstract: Hippo signaling plays a crucial role in growth control and tumor suppression by regulating cell proliferation, apoptosis, and differentiation. How Hippo signaling is regulated has been under extensive investigation. Over the past three years, an increasing amount of data have supported a model of actin cytoskeleton blocking Hippo signaling activity to allow nuclear accumulation of a downstream effector, Yki/Yap/Taz. On the other hand, Hippo signaling negatively regulates actin cytoskeleton organization. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 25 publications
(54 reference statements)
0
29
0
2
Order By: Relevance
“…In some developmental contexts, F-actin negatively regulates HIPPO signaling (Matsui and Lai, 2013). Interestingly, we and others have observed that F-actin is disorganized in PARD6B KD and TFAP2C KD morulae (Alarcon, 2010;Choi et al, 2012).…”
Section: Discussionmentioning
confidence: 57%
“…In some developmental contexts, F-actin negatively regulates HIPPO signaling (Matsui and Lai, 2013). Interestingly, we and others have observed that F-actin is disorganized in PARD6B KD and TFAP2C KD morulae (Alarcon, 2010;Choi et al, 2012).…”
Section: Discussionmentioning
confidence: 57%
“…RhoA activates LIMK through ROCK, and Rac1 stimulates this kinase through PAK (reviewed in (Bar-Sagi and Hall, 2000; Radu et al, 2014), which can explain why ROCK inhibitors do not prevent the activation of YAP by the latter. In turn, how F-actin stimulates YAP was unclear (reviewed in (Matsui and Lai, 2013). YAP is part of multiple cytosolic protein complexes, many of which are driven by the direct interaction between the WW domains of YAP with the PPxY motifs present in most of its associated proteins, including LATS and AMOT (Sudol, 2013; Sudol et al, 2012; Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The actin cytoskeleton has been linked to Hippo signaling (Matsui and Lai, 2013). For example, F-actin regulates Hippo pathway and cell proliferation in the Drosophila wing imaginal disc (Fernández et al, 2011; Sansores-Garcia et al, 2011).…”
Section: Discussionmentioning
confidence: 99%